Optimalisasi Pemanfaatan Pekarangan melalui Peluang Agribisnis Hidroponik di Pesantren Zaadul Ma’ad - Leni Sabrina; Waliah Nur Rahayu; Rismarini Rismarini; Tika Handayani (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Interesting agricultural cultivation technology that is easy to apply by the community, namely hydroponic agribusiness. Plant cultivation techniques without using soil, but using water enriched with nutrients needed by plants. These hydroponic plants are becoming increasingly popular because they are efficient, environmentally friendly, and can be done in limited land. This activity was carried out with the background of raising awareness, knowledge, insight, and skills in cultivating vegetables using the hydroponic method. The form of this activity is socialization carried out and attended by students, administrators and staff of Ma'had Zaadul Ma'ad on Jl. Padat Karya Lorong Melati RT 01, Talang Jambe Village, Sukarame District, Palembang. namely lectures, discussions, and direct practice on hydroponic cultivation. This activity received a good response from PKM participants, where participants enthusiastically followed the course of the workshop activities, namely making hydroponic plant seeds, hydroponic devices, making AB mix nutrients, planting, harvesting, to preparing financial reports. Hydroponic plants have a higher selling value compared to other plants. Of course, this is a potential profitable and promising business opportunity, so that male and female students, administrators and staff can utilize the yard to cultivate hydroponic plants. The prospects for this plant are very bright in the long term because consumer demand never stops. This program has a significant positive impact, but it is recommended that there be further development to expand the reach and sustainability of activities.